“Indigenous” Cooperatives Supporting SDGs Development in Indigenous Communities: a study of social and communication (Case: The Consumer Cooperative of Warga Sauyunan, Kampung Naga, Regency of Tasikmalaya, West Java, Indonesia) - Wawan Lulus Setiawan; Kikin Hidayatullah; Nurul Azizah; Fadya Prayusinar (International Journal of Ethno-Sciences and Education Research, 2023)
The purpose of this study is to describe the role of  cooperative, namely The Consumer cooperative of Warga Sauyunan, in supporting SDGs development in  indegenous community at Kampung Naga, The Regency of Tasikmalaya, West Java, Indonesia. The kampong consists of 101 house-hold and 300 people. This study was based on the background of poverty issues as the main problem faced in Indonesian socio-economy, especially in rural areas, and the issue of sustainability of community development.  Cooperative  development program could be seen as  one effort to reduce poverty   through community based development (CBD) by paying attention to the SDGs principles . This  study used desciptive method. This research resulted in  some findings: (1) cooperative could support the indegenous community in Kampung Naga by promoting their economy, and by strengthening social  ties and network in the communities, (2) cooperative practice  and principles are in line with the social  values and princples of the community in which they always  keep the harmonious  relationship with the nature, (3) indegenous communication pattern of the community is the local wisdom which support cooperative development in indegenous community and SDGs principle.   This research has implications for policies of developing the cooperative development program for other    indegenous communities  in Indonesia. It also has implication on the adoption of cooperative concept and principles by indegenous  people as a new mind-set for more productive, valuable  and sustainable  development.